MicroPython for the Internet of Things A Beginner's Guide to Programming with Python on Microcontrollers - Bell, Charles A. 1962- (Apress L. P., 2024)
This book will help you quickly learn to program for microcontrollers and IoT devices without a lot of study and expense. MicroPython and controllers that support it eliminate the need for programming in a C-like language, making the creation of IoT applications and devices easier and more accessible than ever. MicroPython for the Internet of Things is ideal for readers new to electronics and the world of IoT. Specific examples are provided covering a range of supported devices, sensors, and MicroPython boards such as the Raspberry Pi Pico and the Arduino Nano Connect RP2040 board. Programming for microcontrollers has never been easier. The book takes a practical and hands-on approach without a lot of detours into the depths of theory. It'll show you a faster and easier way to program microcontrollers and IoT devices, teach you MicroPython, a variant of one of the most widely used scripting languages, and is written to be accessible to those new to electronics. After completing this book, and its fun example projects, you'll be ready to ready to use MicroPython to develop your own IoT applications. What You Will Learn Program in MicroPython Understand sensors and basic electronics Develop your own IoT projects Build applications for popular boards such as Raspberry Pi Pico and Arduino Nano Connect RP2040 Load MicroPython on compatible boards Interface with hardware breakout boards Connect hardware to software through MicroPython Explore connecting your microcontroller to the cloud Develop IoT projects for the cloud Who This Book Is For Anyone interested in building IoT solutions without the heavy burden of programming in C++ or C. The book also appeals to those wanting an easier way to work with hardware than is provided by platforms that require more complex programming environments.
Description based upon print version of record. - Conditional Statements
Keywords: Python (Computer program language); Microcontrollers; Computer programming; Python (Langage de programmation); Microcontrôleurs; Programmation (Informatique); computer programming